Auditory neuropathy in pediatric capos syndrome: Favorable outcome with cochlear implant - Santos Santos, Saturnino (2020)
CAPOS syndrome (cerebellar ataxia, areflexia, pes cavus, optic atrophy, and sensorineural hearing loss) is a rare neurological disease, associated with the c.2452G>A mutation in the ATP1A3 gene. We herein report on the phenotypic and genotypic findings of 3 members of an affected Spanish family and the experience of cochlear implant treatment in the youngest of them, a boy who had experienced sensorineural hearing loss with a pattern of auditory neuropathy for 5 years following an initial encephalitic episode when aged 3 years old with very poor outcome using hearing aids. A cochlear implant trial was performed at age 8 years in order to ameliorate his progressive deterioration in audioverbal skills with very poor discrimination. Results evaluation after an 18 months period using CI showed > 80% discrimination in open contexts.